If it's not what You are looking for type in the equation solver your own equation and let us solve it.
16+2x+2x=x-2
We move all terms to the left:
16+2x+2x-(x-2)=0
We add all the numbers together, and all the variables
4x-(x-2)+16=0
We get rid of parentheses
4x-x+2+16=0
We add all the numbers together, and all the variables
3x+18=0
We move all terms containing x to the left, all other terms to the right
3x=-18
x=-18/3
x=-6
| 497=y+256 | | -1/3x-1=-8 | | 0.429-250/x^2=0 | | -5-4m=3-2m | | 13=t-366 | | 0.7x+15=-0.3x-7 | | -250/x^2-0.429=0 | | 9/6=4/n | | -4(n-4)=5n-2 | | y-224=93 | | 2=6x=1-2 | | 2x+4x+88=74 | | t2=729 | | .2.5d2d+4=10+2.5d | | -2x+11=-4 | | 3/5q=-12/11 | | 4(x-1)=2+4x | | 3.57+9g=43.53 | | 3+5p=10 | | 2x+250/x+3.142x/2=0 | | 7(x+3)=9+3x-4 | | 5x+.75=7x+.15 | | v+45=97 | | v-37=316 | | -19=m+5 | | 5x-22=40-4x | | 29=k+5 | | z-14=22 | | f-582=368 | | 1/3x^2-9=0 | | 95=y+14 | | k-48=122 |